Porewater geochemistry of surface sediment of the German North Sea, recovered by mini corer during METEOR cruise MSM99/2 cruise (2021-03-26 - 2021-04-05) - Mark Schmidt (PANGAEA, 2025)
Data set includes geochemical composition of porewater extracted from sediment of the North Sea (German EEZ). Respective sediment was retrieved during RV Maria S. Merian cruise MSM99/2 (Schmidt et al., 2021). Sediments were recovered by using gravity corer, mini-corer, and van Veen grab. Onboard measured parameter (Total alkalinity) and land-based laboratory analyses (Cl, Br, SO4, CH4, B, Mn, Ca, Fe, Na, Mg, Sr, Si, Ba, Li, K) are combined with porosity and water content data. The data is mainly used to evaluate the relevance of porewater chemistry on pockmark formation north of Helgoland (Böttner et al., 2024).